Environment and Galaxy Host Properties of PTA and eLISA Sources. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Palafox, Eva Martínez; Valenzuela, Octavio; Colín, Pedro; Gottlöber, Stefan
Abstract: We use a dynamical model for the decay of supermassive black hole binaries (BHBs) coupled with a cosmological simulation and semi-empirical approaches to the occupation of halos by galaxies and BHs, in order to investigate the properties of galaxies hosting BHBs. We found bimodal distributions of hosts properties, with one peak corresponding to BHBs suitable to be detected by PTAs and the other to BHBs in the eLISA frequency window. We note that for some of the scenarios explored there must be a considerable population of such sources in the nearby Universe that might show detectable EM signatures, representing an important laboratory for multimessenger astrophysics.